Über die Struktur der Menge der Perioden 2-ter Art einer Matrix stetiger Funktionen - Naftalewitsch, A. (Lithuanian Mathematical Journal, 1962)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:А. Г. Нафталевич, О строении множества периодов 2-го рода матрицы непрерывных функцийA. Naftalevičius, Tolydinių funkcijų matricos 2-os rūšies periodų aibės struktūra